Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Flexible V2O5-x nanobelts as SERS tweezers: defect engineering for remarkably sensitive and selective detection - Krishnan, Nikhil; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2026)
Transition metal oxide (TMO)-based semiconductor nanomaterials (NMs) have been progressively explored as promising substrates for surface-enhanced Raman scattering (SERS). The design and synthesis of highly stable, extremely sensitive, exceptionally selective SERS substrates, solely based on defects engineered in TMO-based NMs, have gained significant interest. This work demonstrates a simple hydrothermal route to synthesize substoichiometric V2O5-x flexible nanobelts without the use of surfactants, stabilizing agents, reducing agents, or structure-directing agents. Furthermore, the V2O5-x nanobelts proved to be highly effective as a SERS substrate for the sensitive detection of methylene blue (MB), achieving a remarkable maximum enhancement factor of up to 6.75 & times; 10(9) and a detection limit as low as the picomolar level. This performance is the best among metal oxide semiconductors and is comparable to that of noble metals, even without the presence of a ``hot spot.'' Additionally, the V2O5-x nanobelts demonstrate excellent selectivity as a ``SERS Tweezer,'' enabling the precise detection of MB even in the presence of interfering analytes across binary, ternary, and quinary mixtures. Notably, V2O5-x nanobelts successfully detected melamine and ethephon for the first time using a TMO-based SERS substrate. In addition, the detection limit for SERS using a V2O5-x substrate reached 3 ppm of melamine in liquid milk. Thus, our results clearly demonstrate that metal oxide semiconductors can be transformed into cost-effective, SERS-active substrates through defect engineering. These engineered substrates exhibit high sensitivity, selectivity, stability, recyclability, and biocompatibility-comparable to or even surpassing those of noble metal nanomaterial-based SERS substrates. This advancement could enable their effective use in detecting contaminants in foods and food ingredients.
Keywords: defect engineering; Nanobelts; sensing; SERS; V2O5-x